O postaci Świtezianki-Ondyny w balladzie Mickiewicza = On the figure of Świtezianka-Ondine in Mickiewicz`s ballad - Ruszczyńska, Marta (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
The article is an attempt to interpret the ballad Świtezianka by Adam Mickiewicz in the context of ondine as a mythical charackter. In her search, the author refers to earlier texts, mainly German Romanticism. At the same time, it confirms and complements the relationship of this character with the tradition of myth and fairy tales.
Keywords: Ondyna; woda; romantyzm; mit; fantastyka baśniowa; Ondine; water; romanticism; myth; fairy-tale fantasy